2021
DOI: 10.1007/s00170-021-07474-9
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, hardness, and wear resistance of AZ91 magnesium alloy produced by friction stir processing with air-cooling

Abstract: Friction stir processing (FSP) was used to modify the surface layer of the AZ91 magnesium alloy. The treatment was carried out using a jet cooling nozzle, generating a stream of cold air and enabling intensive cooling of the friction stir processed (FSPed) zone. Single-pass FSP was carried out using a tool rotational speed of 500 rpm and travel speed of 30 mm/min. The treatment was conducted using a truncated cone-shaped tool with a threaded side surface. Strong grain refinement and microstructural changes typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The novelty of the work is an innovative method of cooling the sample during FSP, namely by means of an air stream cooled to −11 °C with a jet cooling nozzle. The proposed solution is located between cooling with compressed air and cooling with cryogenic agents and combines the main advantages of air (cleanliness, no need to remove the coolant from the working area or its disposal/management after treatment) and the advantages of cooling with cryogenic agents (high cooling intensity) [ 52 ]. The advantage of the solution used in this study over air cooling results from the much lower air temperature generated by the jet cooling nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of the work is an innovative method of cooling the sample during FSP, namely by means of an air stream cooled to −11 °C with a jet cooling nozzle. The proposed solution is located between cooling with compressed air and cooling with cryogenic agents and combines the main advantages of air (cleanliness, no need to remove the coolant from the working area or its disposal/management after treatment) and the advantages of cooling with cryogenic agents (high cooling intensity) [ 52 ]. The advantage of the solution used in this study over air cooling results from the much lower air temperature generated by the jet cooling nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…This situation is caused by oxidations that occur with temperature during the FSP. 48 Besides, the Zn ratio in the FSPed AZ31B alloy is higher than the untreated alloy (1.3%), with a value of 2.4%. For the case of FSPed alloy, obtained percentage of Zn ratio of 2.4 is suitable with the literature.…”
Section: Resultsmentioning
confidence: 86%
“…Venkataiah et al [40] observed the increased microhardness values due to the reduction of intermetallic phase and existence of supersaturated grains with Zn solute atoms in friction stir processed (FSP) ZE41 Mg alloy. Iwaszko et al [41] confirmed the improvement in the microhardness by solid solution strengthening caused by β-Mg17Al12 phase dissolution in AZ91 mg matrix during the FSP. These factors also obviously suggest that the changes in the size and distribution of secondary phase and solute atoms promote the strengthening and lead to the improved hardness of microtube in addition to the role of grain size.…”
Section: Impact Of Fsbe Parameters On Microhardness and Corrosion Ratementioning
confidence: 92%